Maternal and fetal outcomes of patients with liver cirrhosis: a case-control study - Xiang Gao; Yunxia Zhu; Haixia Liu; Hongwei Yu; Ming Wang (BMC, 2021)
Abstract Background We aimed to describe the characteristics and outcomes in pregnant women with liver cirrhosis, and identify the predictors of adverse events of mother and fetus. Methods Retrospectively collected mothers with liver cirrhosis in our center from 6/2010 to 6/2019. Women without liver cirrhosis were selected as a control in a 1:2 ratio. The primary assessment was the frequency of maternal and fetal adverse events. The secondary assessment was the adverse events in patients continuing pregnancy or not and the factors to predict the severe adverse events. Results Of 126 pregnancies enrolled, 29 pregnancies were terminated for worrying disease progression and 97 pregnancies continued. One hundred ninety-four pregnancies without liver cirrhosis were selected as control. At baseline, patients with liver cirrhosis have a lower level of platelet, hemoglobin, prothrombin activity, and a higher level of ALT, total Bilirubin, creatinine. Compared to control, patients with liver cirrhosis had a higher frequency of adverse events, including bleeding gums (7.2%vs. 1.0%), TBA elevation (18.6%vs.3.1%), infection (10.3%vs.0.5%), cesarean section (73.6%vs.49.5%), postpartum hemorrhage (13.8% vs 2.1%), blood transfusion (28.9% vs 2.1%), new ascites or aggravating ascites (6.2% vs.0%), MODS (7.2% vs.0.5%) and intensive care unit admissions (24.1% vs 1.1%). The incidence of severe maternal adverse events was also higher (32.0% vs 1.5%). Women who chose to terminated the pregnancy had less severe adverse events (3.4% vs.32.0%). A higher frequency of fetal/infants' complications was observed in liver cirrhosis population than control, including newborn asphyxia (10.2% vs1.1%), low birth weight infant (13.6% vs. 2.6%). In patients who progressed into the third trimester, multivariable regression analysis demonstrated that severe adverse events were associated with a higher CTP score (OR 2.128, 95% CI [1.002, 4.521], p = 0.049). Wilson's disease related liver cirrhosis has a better prognosis (OR = 0.009, 95% CI [0, 0.763], p = 0.038). Conclusions The incidence of the adverse events was significantly increased in pregnancies complicated by cirrhosis. The predictor of severe adverse events is higher CTP score. Wilson's disease induced liver cirrhosis have a better prognosis. Timely termination of pregnancy during the first trimester may avoid the incidence of severe adverse events.